Cardiovascular reactivity is independently associated with better mental health: results from the nationwide German DEGS1 study. Issue 4 (August 2016) - Hassoun, Lina; Meyer, Thomas; Busch, Markus A.; Neuhauser, Hannelore; Scheidt-Nave, Christa; Herrmann-Lingen, Christoph
Abstract : Objective: Using data from the nationwide German DEGS1 study, we assessed whether resting blood pressure (BP) and transient changes in BP are associated with symptoms of depression and quality of life (QoL). Methods: The study included n =4852 adult participants not taking antihypertensives, who completed the Patient Health Questionnaire-9 for assessment of depressive symptoms and the SF-36 for assessment of QoL. Resting BP was defined as the mean of the second and third reading taken at 3-min intervals. Results: General linear models adjusting for age, sex, and BMI showed that both resting BP and short-term BP changes were associated with higher SF-36 mental component summary and lower Patient Health Questionnaire-9 scores. Conclusion: Our data showed that a greater decrease in systolic BP as an indicator for cardiovascular reactivity is related to better mental QoL and fewer depressive symptoms, suggesting a link between BP regulation and mental well-being as part of an adaptive process to mild stressors.